Sport, Homelessness, and Capability: Voices from the Street - Jarvie, Grant (Quest, 2019)
To what extent does soccer increase the capability of the homeless and those living on the street? This study addresses this question by focusing on the ways in which the Homeless World Cup and Street Soccer (Scotland) have impacted upon the lives of some individuals. Primary source data obtained from a series of interviews are situated within Sen’s capability approach to social choice theory. The implications of the study contribute to policy by supporting the idea that sport can contribute as a resource of hope through the development of capability that impacts upon life chances and choices. It adds to a growing number of applied studies of sport that have critically used the work of Sen and it advances the way in which this body of work has been utilized in sport and related areas.